Assessment of Technology Contribution in Digital Lending Transformation Using Technometric and AHP Approach - Satya Dinar Probo Agung; Udisubakti Ciptomulyono (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The rapid development of financial technology (fintech) has accelerated digital transformation in the banking industry, particularly in digital lending services that require effective management of technological resources. However, Bank XYZ has not yet conducted a comprehensive assessment of the contribution of its technological components in supporting digital lending operations. This study aims to measure the contribution of technology and identify strategic priorities for technology development in digital lending services at Bank XYZ. A technometric approach was employed by integrating the Technology Contribution Coefficient (TCC) and Analytical Hierarchy Process (AHP). Data were collected from employees directly involved in digital lending activities and from expert respondents selected based on their experience and involvement in technology management. The analysis focused on four technology components: Technoware, Humanware, Infoware, and Orgaware (THIO). The results show that Technoware has the highest technology contribution (TCC = 0.6931), followed by Orgaware (0.6904), Humanware (0.6794), and Infoware (0.6750). However, AHP results indicate that Humanware is the most strategically important component with a priority weight of 0.388, revealing a gap between actual technology contribution and strategic importance. Furthermore, the State-of-the-Art (SOTA) assessment indicates that Humanware has the lowest maturity level (0.6567), while Infoware requires further enhancement, particularly in analytical capabilities such as scoring engine systems. These findings contribute to the development of an integrated framework for evaluating technology contributions in digital lending and provide practical recommendations for prioritizing human resource development and information management to support sustainable digital transformation in the banking sector.